Pengaruh Waktu Polimerisasi pada Pembentukan Poli Asam Humat Terhadap Efisiensi Dye Sensitized Solar Cell (DSSC) - Nindya Marsha; Hardeli Hardeli (Departemen Kimia FMIPA UNP, 2020)
Abstract— Dye Solar Cell (DSSC) is a solar cell that uses a dye as an absorber of photons from sunlight that will be converted into electrical energy. DSSC research continues in order to obtain DSSC components that will produce high efficiency, inexpensive and environmentally friendly. The number of π bonds in dyes affects the efficiency of DSSC, the more photons from absorbed sunlight will be converted into electrical energy. Polymerization is one of the methods used to increase π bonds in dyes. Polymerization is a combination of several monomers with repeated arrangements. The monomer used in this study is humic acid. Humic acid is an organic compound that has π bonds. Polymerization with humic acid will produce poly humic acid which is used for dyeing in DSSC. The assembled DSSC will be tested for resistance and voltage using a digital multimeter. The dyes will be characterized by UV-VIS and FTIR. UV-VIS test results showed a shift in the higher wavelength region and an increase in absorbance. FTIR characterization was performed to confirm the formation of poly humic acid which was characterized by the presence of formed ether / ester groups. The efficiency of DSSC using polymerized humic acid dye was obtained. The efficiency is higher than that of the humic acid dye which is not polymerized, ie an efficiency of 7,079%. Keywords— DSSC, Polymerization, Humic Acid, Poly Humic Acid.